PSYCHOLOGICAL-PEDAGOGICAL FEATURES OF DEVELOPING STUDENTS' MORAL ATTITUDE BASED ON AXIOLOGICAL APPROACHES - Musurmonov Ochilboy O‘razali o‘g‘li (Web of Journals Publishing, 2024)
In this article, the psychological-pedagogical features of developing students' moral attitude based on axiological approaches are highlighted in a certain sense.
Keywords: Axiological approaches, moral relations, psychological-pedagogical characteristics, behavior, values, person, society, social, strategy.